Ninjurin-1 drives atherosclerosis progression via NF-κB/CXCL-8 activation in endothelial cells - Sun, Zhihong; Ma, Wenjuan; Ye, Feng; Ren, Nana; Shen, Ke; Dong, Nan (Frontiers in Immunology, 2025)
IntroductionAtherosclerosis represents the leading cause of cardiovascular mortality, with persistent inflammation driving residual risk despite lipid-lowering therapies. While Ninjurin-1 (Ninj1) has been implicated in inflammatory diseases, its endothelial-specific role in atherosclerosis remains unclear.MethodsWe conducted integrated molecular, functional, and histological analyses to characterize Ninj1 expression and function in atherosclerosis. Endothelial Ninj1 silencing was performed to assess its effects on NF-κB signaling, CXCL-8 expression, and ox-LDL-induced endothelial dysfunction. In vivo, ApoE-/- mice were treated with the Ninj1 inhibitor mPN12 peptide to evaluate its impact on plaque formation and composition.ResultsNinj1 silencing in endothelial cells suppressed NF-κB signaling and its key inflammatory mediator CXCL-8, conferring protection against ox-LDL-induced endothelial dysfunction by enhancing proliferation and migration while reducing apoptosis (all p < 0.05). In ApoE-/- mice, pharmacological Ninj1 inhibition with mPN12 peptide significantly attenuated plaque development and lipid accumulation while preserving collagen content.DiscussionOur results provide the first evidence that endothelial Ninj1 functions as a novel activator of the NF-κB/CXCL-8 axis, establishing its causal role in atherosclerosis and highlighting its potential as a targeted anti-inflammatory therapy.